Study of epistemological beliefs, attitudes towards learning and conceptual understanding of newtonian force concept among physics education undergraduates - Sim, Sze Kiong (2010)
This research is to probe the epistemological beliefs, learning attitudes and conceptual understanding towards learning Physics among the first year and final year Physics Education undergraduates (N = 68) from Universiti Teknologi Malaysia for 2009/2010 session. This is a descriptive quantitative research. Data are collected by using Physics Epistemological Beliefs & Attitudes Test and Force Concept Inventory. The data analysis indicates that generally the undergraduates hold high sophistication of epistemological beliefs and favorable attitudes in learning Physics. The t-tests also show that there are statistically significant differences in mean scores between first and final year undergraduates for epistemological beliefs and learning attitudes. Higher mean scores in both aspects are in favor of final year undergraduates. However, poor conceptual understanding due to misconceptions is detected among them. Gender differences are detected in both epistemological beliefs and learning attitudes tests which are in favor of female undergraduates. Pearson correlations show that there are some significant relationships between epistemological beliefs, learning attitudes and conceptual understanding. Significant correlation coefficients of .607 at alpha level .01 are detected between epistemological beliefs and conceptual understanding whereas (r = .563) between epistemological beliefs and learning attitudes.